SELF-EFFICACY SEBAGAI PREDIKTOR KESIAPAN MENGAJAR MAHASISWA PAI DALAM PRAKTIK MICROTEACHING - Trisna Levia; Surawan Surawan (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to analyze the effect of self-efficacy on teaching readiness of Islamic Religious Education (PAI) students in microteaching practice at IAIN Palangka Raya. Self-efficacy is defined as an individual's belief in his or her ability to carry out tasks effectively, which in the context of education greatly affects the motivation and performance of prospective teachers. This study used a correlational quantitative approach with a total of 50 respondents of PAI students who were taking microteaching courses. Data were collected through a Likert-scale questionnaire, consisting of 10 items for the self-efficacy variable and 10 items for teaching readiness. The results of descriptive analysis showed that both variables were in the high category. Pearson correlation test yielded a coefficient of 0.769 with a significance of 0.000, indicating a positive and significant relationship between self-efficacy and teaching readiness. Simple linear regression analysis showed that self-efficacy contributed 59.1% to the teaching readiness variable. This finding confirms that self-efficacy is a significant predictor in building teaching readiness of PAI students, and provides important implications in the development of microteaching-based pedagogical training curriculum.